Dangerous games : what the moral panic over role-playing games says about play, religion, and imagined worlds - Laycock, Joseph, 1980- (University of California Press, 2015)
"The 1980s saw the peak of a moral panic over fantasy role-playing games such as Dungeons and Dragons. A coalition of moral entrepreneurs that included the Christian Right, psychologists, and law enforcement claimed these games were not only psychologically dangerous but an occult religion masquerading as a game. Dangerous Games explores both the history and the sociological significance of this panic"--Provided by publisher